2008
DOI: 10.1016/j.neuroscience.2008.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Propentofylline-induced astrocyte modulation leads to alterations in glial glutamate promoter activation following spinal nerve transection

Abstract: We have previously shown that the atypical methylxanthine, propentofylline, reduces mechanical allodynia after peripheral nerve transection in a rodent model of neuropathy. In the present study, we sought to determine whether propentofylline-induced glial modulation alters spinal glutamate transporters, GLT-1 and GLAST in vivo, which may contribute to reduced behavioral hypersensitivity after nerve injury. In order to specifically examine the expression of the spinal glutamate transporters, a novel line of dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 31 publications
4
70
0
Order By: Relevance
“…These potential non–cell‐autonomous effects of dysfunctional astrocytes and microglia in JNCL are expected to synergize with intrinsic neuronal defects to culminate in cell loss 48. These changes led to our interest in investigating the utility of PDE4 inhibitors, because prior studies have shown their efficacy in attenuating microglial proinflammatory activity, augmenting astrocyte glutamate transporter expression, and delivering prosurvival signals to neurons 15, 16, 38. Our findings support a key role for cAMP in dictating motor dysfunction, glial activation, and lysosomal pathology in the Cln3 Δex7/8 brain, and support the feasibility of PDE4 inhibitors as potential therapeutics for the treatment of JNCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…These potential non–cell‐autonomous effects of dysfunctional astrocytes and microglia in JNCL are expected to synergize with intrinsic neuronal defects to culminate in cell loss 48. These changes led to our interest in investigating the utility of PDE4 inhibitors, because prior studies have shown their efficacy in attenuating microglial proinflammatory activity, augmenting astrocyte glutamate transporter expression, and delivering prosurvival signals to neurons 15, 16, 38. Our findings support a key role for cAMP in dictating motor dysfunction, glial activation, and lysosomal pathology in the Cln3 Δex7/8 brain, and support the feasibility of PDE4 inhibitors as potential therapeutics for the treatment of JNCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings support the notion that the decreased expression or function of astrocytic EAATs in the spinal cord resulting from peripheral nerve injury/ inflammation can enhance glutamatergic synaptic neurotransmission and subsequent glutamate-related neuronal adaptation related to pathological pain. It has been reported that propentofylline, an atypical methylxanthine shown to attenuate astrocytic activation as well as pathological pain (10,19), induced the expression of GLT-1 and GLAST in the spinal dorsal horn following spinal nerve transection (35). Furthermore, repeated administration of amitriptyline, a tricyclic antidepressant used as a first-line drug for the treatment of neuropathic pain, reversed the down-regulation of GLT-1 and GLAST in spared nerve injury-model rats (38).…”
Section: Astrocytic Glutamate and Glycine Transporters In Pathologicamentioning
confidence: 97%
“…These findings suggest that glutamate uptake through spinal EAATs plays an important role in maintaining normal pain transmission under physiological conditions. Furthermore, it has been shown that the down-regulation or functional deficiency of glial glutamate transporters in the spinal dorsal horn is associated with diverse models of pathological pain (32,34,35). We have examined the effects of GLT-1 gene transfer into the rat spinal cord using recombinant adenoviruses in inflammatory and neuropathic pain models.…”
Section: Astrocytic Glutamate and Glycine Transporters In Pathologicamentioning
confidence: 99%
“…Some insight may be gained by the application of imaging techniques such as the use of PET ligands at the peripheral benzodiazepine receptor to studies of the temporal pattern of "activation" in patients, but the true therapeutic opportunities offered by this phenomenon can only be realized by well-designed clinical trials coupled to validated biomarkers in patients. Two such examples of pioneering studies in this area involve the compounds ibudilast (95) and propentofylline (96). Propentofylline attenuates pain behaviors in rodent models of neuropathic pain (97,98) and has been shown to modulate inhibitory tone following spinal injury (99) by reducing glial activation via alterations in glutamate promoter activation (96).…”
Section: Mechanisms Based On Activated Microgliamentioning
confidence: 99%
“…Two such examples of pioneering studies in this area involve the compounds ibudilast (95) and propentofylline (96). Propentofylline attenuates pain behaviors in rodent models of neuropathic pain (97,98) and has been shown to modulate inhibitory tone following spinal injury (99) by reducing glial activation via alterations in glutamate promoter activation (96).…”
Section: Mechanisms Based On Activated Microgliamentioning
confidence: 99%